(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Based on the actual baseline data analysis, we clarify the reasons for a sharp decline of discharge of freshwater springs’ discharge (around 7–8 times) within the Ararat Valley. The recorded discharge changes of the springs are mainly, due to the over-exploitation of the confined aquifers (especially the second confined aquifers). As a result, a sharp decline of the piezometric levels of aquifers occurred (up to 15 m and more), which directly affected the discharge of the springs, as they are in close hydraulic connection. In order to correct the existent unfavorable situation, legal, institutional and technical measures are necessary to undertake and implement.